Pseudomonas stutzeri Has Two Closely Related pilA Genes (Type IV Pilus Structural Protein) with Opposite Influences on Natural Genetic Transformation - Graupner, Stefan (American Society for Microbiology, 2001)
Pseudomonas stutzeri has type IV pili for which the pilA gene (here termed pilAI) provides the structural protein and which are required for DNA uptake and natural genetic transformation. Downstream of pilAI we identified a gene, termed pilAII, coding for a deduced protein with a size similar to that of PilAI with 55% amino acid sequence identity and with a typical leader peptide including a leader peptidase cleavage site. Fusions to lacZ revealed that pilAII is expressed only about 10% compared to pilAI, although the genes are cotranscribed as shown by reverse transcription-PCR. Surprisingly, insertional inactivation of pilAII produced a hypertransformation phenotype giving about 16-fold-increased transformation frequencies. Hypertransformation also occurred in pilAI pilAII double mutants expressing heterologous pilA genes of nontransformable bacteria, like Pseudomonas aeruginosa or Dichelobacter nodosus. The overexpression of pilAII decreased transformation up to 5,000-fold compared to that of the pilAII mutant. However, neither inactivation of pilAII nor its overexpression affected the amounts of [(3)H]thymidine-labeled DNA that were competence-specifically bound and taken up by the cells. In the pilAII mutant, the transformation by purified single-stranded DNA (which depends on comA and exbB, as does transformation by duplex DNA) was also increased 17-fold. It is concluded that PilAII suppresses a step in transformation after the uptake of duplex DNA into the cell and perhaps before its translocation into the cytoplasm. The idea that the degree of the transformability of cells could be permanently adjusted by the expression level of an antagonistic protein is discussed.